Meta-Analisis Teori Sinyal: Pengaruh Pengumuman Dividen dan Sinyal Kepemilikan terhadap Nilai Perusahaan - Sunaryono, Sunaryono; Apriani, Tia (Jurnal Ekonomi STIEP, 2025)
This study examines the impact of dividend announcements and ownership signals on firm value using a meta-analytic approach. Prior empirical research reports inconsistent findings regarding the effectiveness of these signals in reducing information asymmetry. A total of 30 published studies were synthesized by converting reported statistics into correlation-based effect sizes (r) and analyzing them using a random-effects model. The results indicate that dividend and ownership signals have a positive and significant influence on firm value, with an overall effect size of r = 0.21. Dividend signals show a stronger effect (r = 0.24) than ownership signals (r = 0.17). Moderator analysis reveals that market type, research method, and signal category contribute to variations in effect sizes. Publication bias tests show no significant bias. These findings reaffirm the relevance of Signaling Theory in explaining market reactions to financial decisions and offer practical implications for corporate decision-makers and investors..